By their words ye shall know them: Evidence of genetic selection against general intelligence and concurrent environmental enrichment in vocabulary usage since the mid 19th century - Menie, Michael A. Woodley of; Fernandes, Heitor B. F.; José Figueredo, Aurelio; Meisenberg, Gerhard (Frontiers in Psychology, 2015)
It has been theorized that declines in g due to negative selection stemming from the inverse association between completed fertility and IQ, and the Flynn effect co-occur, with the effects of the latter being concentrated on less-heritable non-g sources of intelligence variance. Evidence for this comes from the observation that 19th Century populations were more intellectually productive, and also exhibited faster simple reaction times than modern ones, suggesting higher g. This co-occurrence model is tested via examination of historical changes in the utilization frequencies of words from the highly g-loaded WORDSUM test across 5.9 million texts spanning 1850 to 2005. Consistent with predictions, words with higher difficulties (δ parameters from Item Response Theory) and stronger negative correlations between pass-rates and completed fertility presented a steeper decline in use over time, than less difficult and less negatively selected words, which increased in use over time, suggestive of a Flynn effect. These findings persisted when explicitly controlled for word age, literacy rates and temporal autocorrelation. These trends constitute compelling evidence that both producers and consumers of text have experienced declines in g since the mid-19th Century.